Total phenolic content and anti-radical activity of stingless bee honey at different harvesting times - มีชัย อิมรอน; เจ๊ะหลง อิสมะแอ (Progress in Applied Science and Technology, 2018)
The aim of this research was to study on total phenolic content and anti-radical activity of stingless bee honey from three stingless bee species (Geniotrigona thoracica, Heterotrigona itama and Tetragonular larviceps). The samples were harvested 6 times for a period of 1 year. It was found that the total phenolic contents of G.thoracica, H.itama and T.larviceps were in range from 30-500, 90-600 and 50-1,000 mg GAE/100 honey, respectively at the different times of harvesting. In October to November, all stingless bee species gave the lowest content of total phenolic compounds. In addition, T.larviceps had the highest content of total phenolic compounds during in June to July and August to September. The IC50 concentration for anti-radical activity ranged from 25-85, 11-27 and 11-17 mg/mL of G.thoracica, H.itama and T.larviceps, respectively. The data indicated that the honey of T.larviceps showed the best of anti-radical activity. Its IC50 values were similar throughout the year.